MODEL PEMBELAJARAN MENGGIRING SEPAKBOLA BERBASIS PERMAINAN SMP DI KOTA MATARAM TAHUN 2019 - Soemardiawan, Soemardiawan; Yundarwati, Susi (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
The purpose of this research and development is to produce a dribbling football learning model for middle school age in the city of Mataram. In addition, this research and development was carried out to obtain in-depth information about the development and application of a soccer dribbling model for middle school age and to know the effectiveness, efficiency and attractiveness of children towards the models made. This study uses research & development (R & D) research methods from Borg and Gall. The subjects in this research and development were junior high school students consisting of 60 children. The instruments used in this research and development were questionnaires, questionnaires, and the Dribbling football dribbling test instrument used to collect middle school age children, as for the stages in this research and development, at stages: (1) needs analysis, (2) expert evaluation (initial product evaluation); (3) limited testing (small group trials); and (4) main testing (field testing). Test the effectiveness of the model using ball rolling skills to determine the level of soccer dribbling skills for middle school age before giving the treatment in the form of a dribbling model that was developed and to determine the level of dribbling skills after the treatment or treatment of the dribbling model developed. students amounted to 750, then after being given a treatment in the form of a dribbling model obtained the students’ dribbling skill level of 940. Then the model of drawing the ball was effective in improving futsal dribbling learning for junior high school age. Based on the results of the development it can be concluded that: (1) With the dribbling learning model in football for middle school age in the city of Mataram can be developed and applied in physical education learning in schools (2) With the junior high school dribbling learning model that has been developed, there is evidence that this increase is shown in the results of testing the results of pretest and posttest data with significant differences between before and after the treatment model.